2020
DOI: 10.37134/ibej.vol13.sp.3.2020
|View full text |Cite
|
Sign up to set email alerts
|

Organizational justice as a predictor of organizational citizenship behaviour

Abstract: Organizational Justice essential factor could increase the organizational citizenship behaviours among employees in the workplace. This study aims to examine the impact of organizational justice on organizational citizenship behaviours among nurses. The study employed a quantitative method to examine the impact of organizational justice on organizational citizenship behaviours among nurses. The study conducted in Heet General Hospital and the questionnaire tool's used to collect the data. However, the question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
2
0
2
Order By: Relevance
“…Furthermore, they also have a willingness to help their colleagues, give instructions to complete work, and care for other staff members. These results support Chen & Jin (2014), Cropanzano and Rupp (2016), Nisar et al (2014), Al-Quraan & Khasawneh (2017), and Salam (2020.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, they also have a willingness to help their colleagues, give instructions to complete work, and care for other staff members. These results support Chen & Jin (2014), Cropanzano and Rupp (2016), Nisar et al (2014), Al-Quraan & Khasawneh (2017), and Salam (2020.…”
Section: Discussionsupporting
confidence: 81%
“…Many studies have found that fairness ( Salam, 2020 ), a sense of self efficacy ( Zhou and Qian, 2021 ), collective efficacy ( Strydom, 2021 ), and group cohesion ( Schmidthuber and Hilgers, 2019 ) are the antecedents of employees’ ex-role behavior. Engagement in volunteer services or activities gives people an opportunity to show their altruistic values ( Clary et al, 1998 ) and trigger their ex-role behavior.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Organizational citizenship behavior atau OCB diakui sebagai faktor penting dalam organisasi, karena adanya OCB dapat meningkatkan dan memanfaatkan SDM pada organisasi untuk mempertahankan kelangsungan hidup didalam lingkungan yang kompetitif (Benjamin, 2012). Sejalan dengan hal tersebut, Salam (2020) juga berpendapat bahwa OCB merupakan peran penting dalam setiap organisasi, karena sebagai kunci untuk kelangsungan hidup organisasi. Hal ini dikarenakan, OCB dapat diartikan sebagai perilaku ekstra atau lebih di luar pekerjaan formal individu yang sangat dihargai organisasi, karena dapat meningkatkan efisiensi dan daya saing pada bisnis.…”
Section: Pendahuluanunclassified
“…Hal tersebut dapat meyebabkan karyawan dengan sukarela untuk bekerja dengan lembur, dan bahkan bekerja diluar jam kerja mereka (8 jam kerja). Kemudian hal ini juga didukung oleh pendapat Salam (2020), bahwa ketika karyawan melakukan peran lebih mereka secara sukarela (OCB) dapat meningkatkan citra organisasi. Oleh karena itu, dengan adanya tuntutan kerja tersebut diharapkan dapat memberikan kinerja lebih dari tanggung jawab karyawan (OCB), dimana OCB memiliki peran penting dalam berjalannya suatu organisasi (Alzayed et al, 2017).…”
Section: Pendahuluanunclassified